La articulación entre investigación, docencia y extensión en un programa universitario de Nutrición y Dietética (2012)
ABSTRACT: The aim of this study was to explore the integration of teaching, research and service/outreach in a Nutrition and Dietetics undergraduate program. Materials and methods: the study type was a systematization of experiences. Data was collected through group and individual in depth-interviews and also by reviewing documentation. Results: the data collected allowed establishing three main categories of analysis such as: achievements in research, teaching and service/outreach integration, difficulties in the integration, and suggestions that will allow improving it. The program, according to its educational project, has made progress in integrating research, teaching and service/outreach. This was evident in aspects such as student participation in research activities and outreach projects, student internships, and academic practices. There are, however, issues that need to be strengthened. In order to improve the practical component, we recommend defining a policy of student groups that allow articulating teaching, research and service/ outreach within the curriculum, building internal grants for research and outreach for undergraduate students, and developing a program that disseminates outreach work and projects.